Effect of composition and proteolysis on textural characteristics of Croatian cheese ripen in a lamb skin sack (Sir iz mišine) - Rako, Ante, agronom (Array, 2019)
The objective of this study was to determine the effect of composition and proteolysis on textural characteristics of Croatian cheese in a lamb skin sack (Sir iz mišine) over a ripening period of 30 days. Ten ovine milk cheese batches were manufactured according to the traditional manufacturing procedures. The content of total solids, fat, proteins (P<0.05) and salt (P<0.01) significantly increased during cheese ripening. Results of this research showed that αs1-casein hydrolysed more rapid in comparison to the β-casein. An extensive and significant (P<0.05) degradation of αs1-casein was accompanied by significant (P<0.05) accumulation of αs1-I-casein. Although β-casein degradation occurred in cheese to a moderate degree, these changes were not statistically significant. However, the level of γ-casein increased significantly (P<0.01) in cheese throughout ripening. Due to the extensive proteolysis, both TCA-SN (P<0.01) and WSN (P<0.05) significantly increased throughout ripening time. Results showed significant decrease (P<0.05) in hardness, cohesiveness and springiness during cheese ripening along with progress of proteolysis. Weakening effect of caseinolysis predominated over the strengthening effect of moisture loss in the texture development of cheese, which could be attributed to the specific conditions in the animal skin sack during ripening.